Research Article An Analysis of Teachers’ Practices in Instilling Pancasila Student Profile Values through Local Wisdom - Aifan Sumantri; Iis Siti Aisyah; Lud Waluyo Lud (Indonesian Values and Character Education Journal, 2025)
The internalization of the Pancasila Student Profile values represents a strategic step in shaping students’ character in line with the educational transformation promoted by the Merdeka Curriculum. However, challenges such as limited supporting facilities and learning approaches that are less contextual often hinder its implementation. This study aims to analyze teachers’ pedagogical practices in instilling the Pancasila Student Profile values through a local wisdom based approach. The research employs a descriptive qualitative approach with teachers as the primary subjects. Data were collected through participatory observation, in depth interviews, and document analysis, and were thematically analyzed to identify strategies, media, and the impact of integrating local wisdom into learning. Findings reveal that teachers actively utilize local cultural elements, such as mutual cooperation traditions, traditional games, and local legends, as a means of internalizing character values. The local culture based approach not only strengthens students’ understanding of Pancasila values but also enhances active participation and emotional engagement in the learning process. Based on these results, it can be concluded that integrating local wisdom into learning practices significantly contributes to strengthening character education and has the potential as a relevant contextual pedagogical model. The implication is that teachers can adapt local wisdom based approaches to improve the effectiveness of character education across various educational settings.